PELATIHAN PERTOLONGAN PERTAMA PADA KECELAKAAN (P3K) DI SMP AR–RISALAH KECAMATAN LUBUKLINGGAU TIMUR 1 KOTA LUBUKLINGGAU - Nadi Aprilyadi; Zuraidah Zuraidah; Yeni Elviani; Marta Pastari (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT, POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN PALEMBANG, 2019)
Accident refers to an event that occurs unintentionally. For example, traffic accidents, accidents with sharp objects and so on. The word accident is taken from the root word accident. The addition of the affixes